Immanent critique as a social physiognomics of appearance: Adorno’s account of the modern possibilities of experience - De Cosmo, Chiara (Scenari, 2022)
The aim of my paper is to focus on the notion of “social physiognomics of appearance”, which Adorno formulated in his Introduction to the so-called Positivismusstreit (1961). At first, I would linger on the characteristics of this approach, by crossing the Adorno’s mature works and showing their deep bond with Benjamin’s reflections. In the second part of my paper I would like to underline how Adorno gives a different meaning to the notion of “physiognomy”, grounded on the importance of conceptual mediation. He stresses the need to unfold the logical stratification of “facts”, instead of considering them as a pure monadological expression of totality. According to him, this operation requires a form of interpretation that keeps its imaginative trait, i.e. the ability to disclose the temporal sedimentation of things. In this sense this kind of creative interpretation can represent a new form of experience, that goes beyond the non-historical dimension of modern phantasmagoria.